A utilização de softwares educativos e métodos de ensino no estudo de poliedros e corpos redondos - Araújo, Ciandra Augusta de (2017)
In this study some proposals are presented for the teaching of polyhedrons and round bodies. The choice of this topic was based on the fact that many students have difficulty in learning spatial geometry in the way it is commonly taught. Starting from this supposition, several activities that help students to visualize spatial figures will be explored. The objective of this work is to make the learning process easier, so that students may better understand the content and be able to resolve the problems presented to them. The methodological approach was bibliographical research in books and on the internet, as well as field study, in which the proposed activities were applied and data collection was carried out. The sample was composed of students from the 3rd year of Senior High School linked to the Technical Course in Electro-mechanics at the Federal Institute of Education, Science and Technology of Mato Grosso, Primavera do Leste Campus. One of the main results of this research refers to how the use of educational software and folding activities contributed to the visualization of spatial figures. Another refers to how the use of other methodologies helped in the students? learning process; it was notable that none of the teaching methods proposed had already been used by the teachers of the students in the sample group. The other results obtained are reported at the end of the work.